Impact of post‐void residual urine volume on intravesical recurrence after nephroureterectomy for upper urinary tract urothelial carcinoma. (14th September 2019) - Sazuka, Tomokazu; Sakamoto, Shinichi; Nakamura, Kazuyoshi; Imamura, Yusuke; Yamamoto, Satoshi; Komiya, Akira; Ichikawa, Tomohiko
Abstract : Objective: To examine the impact of post‐void residual urine volume on the risk of postoperative recurrence of intravesical carcinoma in patients with upper urinary tract urothelial carcinoma undergoing nephroureterectomy. Methods: We retrospectively reviewed the data of 81 patients who were admitted to Chiba University Graduate School of Medicine Hospital and underwent nephroureterectomy for upper urinary tract urothelial carcinoma without bladder carcinoma. We assessed the predictive factors for intravesical recurrence after nephroureterectomy in all patients. Next, we compared patients with and without a residual urine volume using propensity score‐matching analysis. The presence of a residual urine volume was defined as ≥30 mL. Results: The median follow‐up period among all patients was 48 months. The presence of pyuria and a residual urine volume were associated with bladder recurrence in the multivariate analysis. A total of 19 patients each were selected after matching, and we confirmed a significant difference between the presence and absence of a residual urine volume ( P  = 0.0291). The 2‐year postoperative recurrence‐free rate of patients with and without a residual urine volume was 32% and 82%, respectively. Conclusions: This is the first study to evaluate the post‐void residual urine volume and intravesical recurrence rate after nephroureterectomy for upper urinary tract urothelial carcinoma. The presence of residual urine might be a risk factor for postoperative recurrence of intravesical carcinoma.